Initial thoughts concerning the policy directions and measures for development and application of iot toward 2025 in Vietnam - Duong, Duong Khanh; Sinh, Bach Tan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2021)
As a middle-income country, Vietnam can exploit the opportunity provided by the 4th Industrial Revolution to rapidly transition from a resource-driven growth model to a productivity and efficiency driven growth with a gradual approach to innovation-based growth. The Internet of Things is an area of great potential that can help Vietnam achieve that expectation if Vietnam chooses a suitable way for itself. The article presents some initial thoughts on views, principles and measures to build policy directions and solutions for developing and applying IoT in Vietnam to 2025. Code: 20112401